Assessment of safety of enterococci isolated throughout traditional Terrincho cheesemaking: virulence factors and antibiotic susceptibility - Pimentel, L.L; Semedo, T; Tenreiro, R; Crespo, M.T.B; Pintado, M.M.E; Malcata, F.X (Journal of food protection, 2007)
Enterococci account for an important fraction of the adventitious microflora of traditional cheeses manufactured in Mediterranean countries from small ruminants' raw milk and play an important role in the development of suitable organoleptic characteristics of the final product. It has been suggested that animals used for food or animals that supply edible products are a reservoir of antibiotic-resistant enterococci. The main purpose of this research effort was thus to identify, to the species level, a total of 73 enterococci with high tolerance to acidic pH and bile salts (as prevailing environmental conditions in the first portion of the gastrointestinal tract), which were previously isolated from the milk feedstock to the final product of Terrincho cheesemaking, and to determine their profiles of antibiotic susceptibility, coupled with the occurrence of specific virulence factors (especially in those that might eventually be claimed to exhibit suitable probiotic and technological performances). Isolates, identified by both API 20 STREP and PCR methods, were found to belong to the following Enterococcus species: E. casseliflavus, E. durans, E. faecalis, E. faecium, and E. gallinarum. Susceptibility of those isolates was observed to most antibiotics tested, whereas none harbored aminoglycoside resistance genes. PCR screenings for cytolysin genes (cylL(L), cylL(s), cylM, cylB, and cylA), surface adhesin genes (efaA(fs), efaA(fm), and esp), the aggregation protein gene (agg), and the extracellular metalloendopeptidase gene (gelE) were performed. All isolates proved negative for cylL(L), cylM, cylB, and agg genes. Both E. faecalis strains were positive for the cell wall-associated protein Esp and the cell wall adhesin efaA(fs), whereas the cell wall adhesin efaA(fm) was detected in 11 of the 12 E. faecium strains. Only one strain possessed the cylL(s) determinant, and another possessed the cylA gene. Incidence of virulence determinants was thus very low; hence, the enterococcal adventitious microflora tested is essentially safe.